The Most Commonly Used Diet Supplements for Hair, Skin and Nails in the Opinion of Pharmacy Employees from Different Cities in Poland - Jachimowicz-Rogowska, Karolina; Sowińska, Lesya; Winiarska-Mieczan, Anna; Kolasa, Katarzyna; Fabjanowska, Julia (Najczęściej stosowane suplementy diety na włosy, skórę i paznokcie w opinii pracowników aptek z różnych miast na terenie Polski, 2022)
Preparations influencing the condition of hair, skin and nails constitute an important group of dietary supplements. They contain active substances that positively influence condition and appearance of skin. The aim of the study was to identify the most frequently used dietary supplements for hair, skin and nails in the form of tablets, and to verify the effects of the active ingredients declared on the basis of the literature. The most common ingredients in hair, skin, and nail supplements were biotin, zinc, copper, vitamin C, and niacin. Most of the selected dietary supplements were multi-ingredient, and the content of ingredients in one dose of supplements varied greatly. Almost all the ingredients contained in the analysed dietary supplements have an effect confirmed in the literature; one of those (PABA) has no proven effectiveness. There is a need for more research into hair, skin and nail nutritional supplements and into consumer choices.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2022, Nr 38, s. 60-74
Keywords: dietary supplements; nutricosmetics; hair; skin; nails; pharmacist; suplementy diety; nutrikosmetyki; włosy; skóra; paznokcie; farmaceuta